KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN SISWA - Dewinta, Dewinta (Jurnal Pembelajaran Prospektif, 2025)
This study aimed to characterize the extroverted and introverted personality types of SMP Negri 23 Pontianak students in relation to their mathematics communication abilities.The qualitative descriptive method was employed in this investigation.The research subjects in this study were 20 grade VIIID students of SMP Negeri 23 Pontianak. Students are given a quiz pertaining to personality types that is filled out according to the Eysenck Personality Inventory (EPI) personality type test. Students then take a mathematical communication skills test with a total of six questions. The study's findings indicate that introverted personality types are more likely to have kids with mathematical communication skills who can write information and comprehend difficulties when solving problems, while in extroverted students, Students who possess this particular personality type are problem solvers. The problem solver has not been able to comprehend the intent of the problem and solve it. Keywords : Mathematical communication skills, Peronality types.